Analysis of sheep and goat milk production by development regions and forms of property in the period 2010-2018 - Alexandra Marina Manolache (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
This paper proposes the analysis of forms of ownership (total, private sector, individual farms), for the eight development regions for sheep and goat milk. This paper is based on the analysis of statistical data from a quantitative and qualitative point of view, highlighting the contribution of each development region and the evolution of sheep and goat milk production in the period 2010-2018. At the end, a comparison will be made with the level of production depending on the change of ownership structure, in order to determine the correct sample according to its ownership form. Given the importance of milk both as a product in human nutrition and the role it plays in the economies of EU member states, the milk and dairy market has been and is one of the common markets, which has been dealt with extensively by regulations. it could become a globally competitive market.
Keywords: E20; Q10; 330; milk; evolution; production; sheep and goat